#5**-1 **

\((1+x+x^2+......+x^{14})^2\\~\\ =1+2x+3x^2+ .........+15x^{14}+14x^{13}+13x^{12}+............2x^{27}+x^{28}\)

so the product is:

\((1+x+x^2+x^3+.......x^{27})(1+2x+3x^2+ .........+15x^{14}+14x^{13}+13x^{12}+............2x^{27}+x^{28})\\ \)

I am interested in the sum of the x^28 coefficients.

This is it

2+3+....+14+15 +14+13+......+2+1

=2(2+3+4+5+6+7+8+9+10+11+12+13+14)+15 +1

= 224

So the coefficient of x^28= **224**

-------------------

Maybe BaldisBasics knows a short cut but he certainly has not explained it to me.

Melody Mar 15, 2019